Coronary sinus fetuin and sodium levels are independently associated with all-cause mortality in patients awaiting heart transplantation. (25th November 2020) - Szczurek, W; Gasior, M; Skrzypek, M; Romuk, E; Zembala, M; Malyszek-Tumidajewicz, J; Szygula Jurkiewicz, B
Abstract: Background: Risk stratification is a critical component of selection process of the patients with end-stage heart failure (HF) who are considered for heart transplantation (HT). Due to the constantly increasing number of the patients placed on the transplant waiting lists and a global shortage of organs available for HT, the key issue becomes an accurate risk stratification of death and proper organ allocation to these patients who will benefit the most from this form of treatment. Purpose: The aim of this study was to identify the factors associated with mortality during a 1.5-year follow-up in patients with end-stage HF awaiting HT. Methods: We prospectively analysed 72 patients with advanced HF awaiting HT at our institution between 2015 and 2016. At the time of inclusion in the study routine laboratory tests, cardiopulmonary exercise test, echocardiography, and right heart catheterisation were performed in all patients. During right heart catheterisation, 10 ml of coronary sinus blood was collected. Fetuin serum concentration was measured by the sandwich enzyme-linked immunosorbent assay (ELISA) with the commercially available kit.The end-point was defined as all-cause mortality during a 1.5 years follow-up. Our medical university local Institutional Review Board approved the study protocol, and all patients provided informed consent. The study was performed in accordance with the ethical standards as laid down in the 1964 Declaration of Helsinki and its later amendments. Results: Patients' median age was 53.00 (46.00–58.00) years, and 91.7% were men. During the 1.5-year follow-up, 31 (43.1%) patients died. The area under the receiver operating characteristic curve indicated a good discriminatory power of fetuin (AUC: 0.917 [95% CI: 0.858–0.977]). The cut-off point for fetuin (<632.36) had a sensitivity of 87% and a specificity of 83%. Patients with a lower fetuin level had a significantly worse 1.5-year survival compared to the group with a higher fetuin level (20.6% versus 89.5%; (long rank p<0.001). Fetuin OR 0.990 (0.986–0.996); p<0.001) and plasma sodium levels (OR, 0.640 [0.464–0.882]; p<0.001) were independent predictors of death during 1.5-year follow-up period. Conclusions: Our study demonstrated that a low coronary sinus fetuin and peripheral blood sodium levels are associated with mortality patients with advanced HF accepted for HT. In addition, fetuin level, with excellent prognostic strength, allows for the risk stratification of death in analysed group of patients. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Medical University of Silesia